Layanan Bimbingan dan Konseling untuk Meningkatkan Resiliensi Siswa Korban Bullying: Sebuah Kajian Sistematis - Irawan, Tb. Moh. Irma Ari; Hamzah, Rifqy Muhammad; Mulyati, Srie (UPT Publikasi dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2024)
The issue of bullying among students necessitates serious attention due to its potential psychological consequences, such as trauma and even depression. Implementing strategies to enhance students' resilience through guidance and counseling services is crucial for mitigating the psychological impacts of bullying. This study aims to explore the implementation of guidance and counseling services that can effectively improve the resilience of students who have been victims of bullying. The research methodology employed is a literature review, analyzing journals available on Google Scholar and Publish or Perish from the years 2017 to 2024. The keywords used to gather information include